The Urgency of Making Notary Deeds Electronically during the Covid-19 Pandemic - Rizal Mutaqin (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
One of the professions that is given the authority to make an authentic deed is a notary. There are three forms of state emergency status, namely civil emergency, military emergency, disaster emergency, and public health emergency. During the Covid-19 pandemic as it is today, electronic transactions are mostly carried out to reduce physical contact between humans which can increase the possibility of the spread of the Covid-19 virus. Considering the Law on Notary Positions requires that the deed be made before a notary. The author in this study used a normative juridical approach. Normative legal research is legal research that puts the law as a building system of norms. Data analysis was carried out qualitatively, namely from the data obtained and then compiled systematically and analyzed to achieve clarity of the problems discussed, which were described qualitatively. The urgency of making a notary deed electronically during the Corona Virus Disease (Covid-19) pandemic is that the implementation of the deed must still be carried out with the help of an electronic system, considering the Covid-19 pandemic. Indonesia is a country that has recognized the validity of electronic information or documents to be used as legal evidence before the law and courts, known as electronic evidence in Act No. 11 of 2008 and its renewal in Act No. 19 of 2016 concerning Information and Electronic Transactions (hereinafter referred to as UU ITE). The legal position of a notarial deed made electronically. The legal position of a notary deed made electronically is the provisions of the laws and regulations governing the making of an authentic deed both in the Notary Position Act and Government Regulation Number 37 of 1998 concerning Land Deed Maker Officials and their amendments principally prioritize direct, face-to-face interaction and attendance parties who wish to be notary. This provision is as regulated in Article 1868 Burgelijk Wetboek (hereinafter referred to as BW) or the Civil Code which states that a deed is called an authentic deed if it meets the requirements, namely the form of the deed is determined in the laws.